(untitled) (Research, Society and Development, 2021)
Introduction: Cerebral palsy (CP) is characterized by brain damage in the early stages of development, and may be associated with spasticity. In view of the normalization of muscle tone, botulinum toxin (BT) is an alternative to provide greater relaxation of the muscles in patients with spasticity. Physiotherapy treatment associated with the use of toxin could enhance the treatment for spasticity. Objective: To review the literature on physical therapy treatment associated with the use of TB in patients with spastic cerebral palsy. Methods: A literature review was conducted in PubMed, LILACS, BVS and SciELO databases, from 2010 to 2020. The descriptors used were: cerebral palsy, spasticity, botulinum toxin and physical therapy. Results: 77 articles were found, however, 8 were excluded for being duplicates and 60 for not meeting the inclusion criteria, being included 9 articles in this review. In the reviewed studies, TB when associated with physical therapy treatments, promoted the relaxation of spastic muscles, reduced pain, favored the use of orthoses, increased the range of motion, improving the quality and life expectancy of these individuals. Final considerations: The use of TB associated with physical therapy provides improvement on spasticity and functionality in patients with spastic CP.